The reconnection with a deceased loved one through virtual reality. Opinions and concerns against an unprecedented challenge - Nikolaou (Νίκη Νικολάου) Niki (Bioethica, 2020)
A team of documentary producers and computer programmers, while they were in a laboratory creating a virtual reality environment, could never have imagined how much impact their project would have not only to the family involved but also to a large percentage of humanity and other scientific fields. In particular, they created a virtual park and a virtual girl, who in real life had died, and, through the special equipment, they placed the living mother in this environment. The mother ‘‘met’’ her daughter, ‘‘touched’’ her, ‘‘talked’’ to her, they celebrated her daughter’s birthday together’’ and, at the end, they ‘‘said goodbye’’ to each other. This endeavor was the result of a combination of techniques and elements of various sciences. Of course it is admirable, but at the same time it raises doubts, intense concerns and many questions such as: ‘‘What are the limits of the technological applications?’’; ‘‘What aspects and at what extent of the human existence can they involved?’’; ‘‘How is the human existence affected?”; Can an application play with human emotions and, specifically, with the pain and misery of a human, in this case of a mother mourning her child?’’ The issue is difficult and even more difficult the moral and bioethical dilemmas that arise. All the above-mentioned will be presented and studied in this present article. In particular, initially reference will be made to the definition of virtual reality, to the means which lead to the achievement of a completely operational system, as well as to the areas of application of its systems. Therefore, the way of creation and the context of the documentary will be presented, to be followed by a very short reference to the thoughts that the mother of the girl had expressed. Afterwards various opinions will be presented, questions and dilemmas arising by the documentary will be mentioned and commented and alongside some questions will be asked for reflection. The conclusions will complete this present article.